Prevalence of Merkel Cell Polyomavirus in Normal and Lesional Skin: A Systematic Review and Meta-Analysis - Wijaya, Wilson A.; Liu, Yu; Qing, Yong; Li, Zhengyong (Frontiers in Oncology, 2022)
The prevalence of Merkel cell polyomavirus (MCPyV) in Merkel cell carcinoma (MCC) and non-MCC skin lesions and its possible role in the etiology of other skin diseases remain controversial.To systematically assess the association between MCPyV infection and MCC, non-MCC skin lesions, and normal skin. For this systematic review and meta-analysis, a comprehensive search for eligible studies was conducted using Medline Ovid, Pubmed, Web of Science, and the Cochrane CENTRAL databases until August 2021; references were searched to identify additional studies. Observational studies that investigated the association between MCPyV infection and MCC, non-MCC skin lesions, and normal skin using polymerase chain reaction (PCR) as a detection method and provided sufficient data to calculate the prevalence of MCPyV positivity. A total of 50 articles were included in the study after exclusion criteria were applied. Two reviewers independently reviewed and assessed the eligibility of the studies, and all disagreements were resolved by consensus. To determine the association between MCPyV and MCC, overall odds ratio (OR) were calculated with 95% CI using a random-effects model. Single-arm meta-analyses were performed to examine the prevalence rate of MCPyV positivity in MCC, non-MCC skin lesions, and normal skin. The primary analysis was the prevalence rate of MCPyV in MCC. Secondary outcomes included the prevalence rate of MCPyV in non-MCC skin lesions and normal skin. A total of 50 studies involving 5428 patients were reviewed based on our inclusion and exclusion criteria. Compared with the control group, MCPyV infection was significantly associated with MCC (OR = 3.51, 95% CI = 2.96 - 4.05). The global prevalence of MCPyV+ in MCC, melanoma, squamous cell carcinoma, basal cell carcinoma, Bowen’s disease, actinic keratosis, keratoacanthoma, seborrheic keratosis, and normal skin was 80%, 4%, 15%, 15%, 21%, 6%, 20%, 10%, and 11%, respectively. The current results suggest that MCPyV infection is significantly associated with an increased risk of MCC. However, the low prevalence rate of MCPyV+ in non-MCC skin lesions does not exclude a pathogenic association of this virus with the development of non-MCC skin lesions.